2018
DOI: 10.1093/bjsw/bcy103
|View full text |Cite
|
Sign up to set email alerts
|

Youngsters’ Perspectives on Continuity in Their Contacts with Youth-Care Services

Abstract: Continuity is seen as an important aim for the quality of youth-care services. However, views on continuity are predominantly guided by experts, without much attention to user perspectives. This paper focuses on youngsters’ experienced continuity in relation to youth-care services. Twenty-five youngsters, who were in residential care or reached by low-threshold youth services, were interviewed about their experiences in and out of care. In thematically exploring the biographical narratives for important experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Consequently, these interventions might not be able to acquire the mandate to have a real impact on adolescents' lives. A comparable tendency was noticed in research on continuity of care, where adolescents expressed a lack of connection with youth care due to an overemphasis on individual problem definitions and labeling (Naert et al, 2018). Moreover, as these intervention programs are experienced as mainly trying to impose a normative ideal of "a good life," adolescents' own aspirations and conceptions of important issues are left unanswered.…”
Section: The Role Of Professional Support and A Mandatory Stay In A CImentioning
confidence: 82%
“…Consequently, these interventions might not be able to acquire the mandate to have a real impact on adolescents' lives. A comparable tendency was noticed in research on continuity of care, where adolescents expressed a lack of connection with youth care due to an overemphasis on individual problem definitions and labeling (Naert et al, 2018). Moreover, as these intervention programs are experienced as mainly trying to impose a normative ideal of "a good life," adolescents' own aspirations and conceptions of important issues are left unanswered.…”
Section: The Role Of Professional Support and A Mandatory Stay In A CImentioning
confidence: 82%
“…For youngsters in our study, continuity of care is a complex subject. The experience of continuity in their lives is about much more than the presence of youth care interventions or youth care workers (Naert et al., 2019), whereas in the literature concerning continuity of care, the dominant rationale is on seamless care trajectories leading to closed circuits that prevent youngsters from falling through the cracks of the system (Naert et al., 2019). However, in the narratives of youngsters, while youth care interventions were present, they still experienced discontinuity.…”
Section: Discussionmentioning
confidence: 99%
“…The identified strategies are also linked to a mismatch in timing of youth care interventions with what is needed at different points in the life trajectories of youngsters. The absence of support at critical moments is seen as most problematic in relation to experienced continuity (Naert et al., 2019; Pinkerton and Rooney, 2014). The timeliness of interventions can be defined as ‘ getting help when needed ’ (Biringer et al., 2017: 6) and is of great importance, as it determines new relations with service providers.…”
Section: Discussionmentioning
confidence: 99%
“…While governmental agencies such as corrections and probation departments can facilitate the processes and determine their own willingness to enforce them, it is important to RJ that the essential people develop and agree to content and goals in their restoration plans. Across human and social services, researchers find that people who are prescribed interventions by agencies often feel they have no say in the services or treatment (Naert et al, 2019; Riley & Hayes, 2018; Signorini et al, 2018) and that the treatments do not relate to the needs they see in their daily lives (Altschuler & Armstrong, 2002; Altschuler et al, 1999). Such perceptions can demotivate commitment and adherence to treatment plans.…”
Section: Restoration Through Happinessmentioning
confidence: 99%
“…Such perceptions can demotivate commitment and adherence to treatment plans. There are several reasons for this, including disconnects between providers and clients’ lives (Altschuler & Armstrong, 2002; Altschuler et al, 1999), lack of coordination of care among providers themselves (Naert et al, 2019; Psaila et al, 2014; Signorini et al, 2018), unavailability of services or inconvenient available times for services (Liao & White, 2014), and a belief from professionals that they are the ones best suited to oversee clients’ treatments and lives (Psaila et al, 2014). Focusing efforts on holistic, strengths-based interventions developed through direct, active engagement of the essential people can improve acceptance, support for, and achievement of interventions (Naert et al, 2019; Signorini et al, 2018), including the steps to repair harm identified in restoration plans.…”
Section: Restoration Through Happinessmentioning
confidence: 99%